THE INFLUENCE OF THE USE OF AUDIOVISUAL MEDIA ON THE EXPRESSIVE LANGUAGE ABILITIES OF EARLY CHILDREN IN KINDERGARTEN - Intisari; Nurlaelah; Amri, Nur Alim; Hajerah; Hasbur, Heni Safitri (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2024)
Expressive language proficiency plays a crucial role in everyday life, allowing children to express their needs and desires more easily and helping others to understand them better. However, the challenge of developing these skills, particularly in young children, remains a key issue in education. This study aims to assess the impact of audiovisual media on improving the expressive language abilities of children at Chamsiyah Kindergarten, located in Ulugalung Village, Bantaeng Regency. The research adopted a quantitative approach using a quasi-experimental design. Data was gathered through observations in a one-group pretest and posttest format. The educational tool employed was audiovisual media. The sample consisted of 15 children aged 5 to 6 years who voluntarily participated in the study. The analysis revealed a significant increase in the average scores between the pretest and posttest. Hypothesis testing showed that the t-statistic was -15.427, compared to a t-table value of 1.761, indicating that the t-statistic was greater than the t-table value, supporting the acceptance of the alternative hypothesis (Ha). Thus, it was concluded that the use of audiovisual media significantly enhanced the expressive language skills of early childhood learners. This research contributes to early childhood education by demonstrating the practical effectiveness of audiovisual media as a tool to support the development of expressive language skills in children.